The United States of America and Decolonization in the South Pacific Region Countries - David Home (GoAcademica Research & Publishing, 2019)
The purpose of this study is intended to reveal the background and influence of the United States in the South Pacific countries. The method used in this study is critical history. In analyzing data, the steps taken are steps according to Kuntowijoyo, topic selection, heuristics, verification (source criticism), interpretation, historiography. The results showed that the presence of the Soviet Union and China in the south Pacific moved the United States to pay more attention to this region, by further enhancing its role in the South Pacific Region. The role of the United States in the South Pacific Region covers the fields of economics, politics, and strategy. In the economic field, the United States provides assistance and improves their standard of living. In the political and strategic fields, the United States, together with Australia and New Zealand, which was bound by the ANZUS defense pact, tried to stem the influx of communist influence from the Soviet Union and China.